2007
DOI: 10.1002/anie.200703655
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Fullerenes in a Helical PMMA Cavity Leading to a Robust Processable Complex with a Macromolecular Helicity Memory

Abstract: A commodity plastic, syndiotactic poly(methyl methacrylate) (st‐PMMA), has been found to fold into a right‐ or left‐handed helix through the assistance of (R)‐ or (S)‐1‐phenylethanol (1) and encapsulates fullerenes within its helical cavity to form a robust, processable, and optically active peapod‐like complex whose helicity is retained after removal of the chiral alcohols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
175
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(187 citation statements)
references
References 41 publications
9
175
1
2
Order By: Relevance
“…The st-PMMA/C 60 complex gels, which contained no trace amount of 6, showed mirror-imaged VCDs in the PMMA IR regions due to the preferred-handed helicity (a) and also ECDs in the encapsulated C 60 chromophore regions (b). The VCD intensities of the st-PMMA/C 60 complex gels at around 1150 and 1280 cm ¹1 were approximately three times larger than those prepared with (S)-and (R)-1 (20 vol %), 3 indicating the remarkable increase in the helical sense excess of the st-PMMA induced by (S)-and (R)-6. 14 The ECD measurement results of the st-PMMA/C 60 complexes assisted by optically active liquids are summarized in Table 1, which revealed that the use of optically active solvents (Entries 813), in particular, the aromatic optically active primary (6 and 7) and secondary (911) amines more efficiently induced an excess one-handedness in the st-PMMA backbone, thus showing intense ECDs in the C 60 -chromophore regions as compared with those induced by chiral additives (Entries 24).…”
Section: 13mentioning
confidence: 86%
See 2 more Smart Citations
“…The st-PMMA/C 60 complex gels, which contained no trace amount of 6, showed mirror-imaged VCDs in the PMMA IR regions due to the preferred-handed helicity (a) and also ECDs in the encapsulated C 60 chromophore regions (b). The VCD intensities of the st-PMMA/C 60 complex gels at around 1150 and 1280 cm ¹1 were approximately three times larger than those prepared with (S)-and (R)-1 (20 vol %), 3 indicating the remarkable increase in the helical sense excess of the st-PMMA induced by (S)-and (R)-6. 14 The ECD measurement results of the st-PMMA/C 60 complexes assisted by optically active liquids are summarized in Table 1, which revealed that the use of optically active solvents (Entries 813), in particular, the aromatic optically active primary (6 and 7) and secondary (911) amines more efficiently induced an excess one-handedness in the st-PMMA backbone, thus showing intense ECDs in the C 60 -chromophore regions as compared with those induced by chiral additives (Entries 24).…”
Section: 13mentioning
confidence: 86%
“…3 In addition, preferredhanded helical structures in st-PMMA and its complex with fullerenes could be induced in the presence of an optically active alcohol 1 3 and amine 6 4,5 as an additive and solvent, respectively, as evidenced by electronic circular dichroism (ECD) induced in the encapsulated-C 60 -chromophore regions and vibrational CD (VCD) in the PMMA IR regions. Furthermore, the induced st-PMMA helix was retained ("memorized") 68 after complete removal of the chiral molecules (Scheme 1) 3 and could recognize the size and chirality of higher fullerenes through an induced-fit mechanism to selectively extract enantiomers of the higher fullerenes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In those conditions, the interactions of the polymer with the support and the character and evaporation rate of the solvent are critical factors. In contrast, the Langmuir-Blodgett (LB) method prepares monolayers in an air/water interphase, 74,75 and therefore, the hydrophilic/hydrophobic character of the polymer and the solid support play a very important role. Tang and co-workers studied the formation of monolayers by this technique, using PPAs with hydrophobic backbone and bearing hydrophilic pendants such as amino acid residues.…”
Section: Langmuir-blodgettmentioning
confidence: 99%
“…Their numerous applications in materials science include optical, magnetic, electronic, catalytic, and biological applications. [1][2][3][4][5][6][7][8] In particular, many researchers have examined exohedral metallofullerene complexes to investigate and understand the effects of metal (M) coordination on the chemical and physical properties of C 60 , as well as the reactivities and electrochemical properties of these complexes, ultimately to develop new electronic nanomaterials and nanodevices. [9][10][11][12][13][14] Although every carbon atom in C 60 is chemically equivalent, the structure of C 60 offers many different possible bonding sites and modes of interaction with metals.…”
Section: Introductionmentioning
confidence: 99%